Exploring the multifaceted antitumor activity of axitinib in lung carcinoids - Oldani, Monica; Cantone, Maria Celeste; Gaudenzi, Germano; Carra, Silvia; Dicitore, Alessandra; Saronni, Davide; Borghi, Maria Orietta; Lombardi, Angela; Caraglia, Michele; Persani, Luca; Vitale, Giovanni (Frontiers in Endocrinology, 2024)
Introduction: Lung carcinoids (LCs) are a type of neuroendocrine tumor (NET) that originate in the bronchopulmonary tract. LCs account for 20-25% of all NETs and approximately 1-2% of lung cancers. Given the highly vascularized nature of NETs and their tendency to overexpress vascular growth factor receptors (VEGFR), inhibiting angiogenesis appears as a potential therapeutic target in slowing down tumor growth and spread. This study evaluated the long-term antitumor activity and related mechanisms of axitinib (AXI), a VEGFR-targeting drug, in LC cell lines. Methods: Three LC cell lines (NCI-H727, UMC-11 and NCI-H835) were incubated with their respective EC50 AXI concentrations for 6 days. At the end of the incubation, FACS experiments and Western blot analyses were performed to examine changes in the cell cycle and the activation of apoptosis. Microscopy analyses were added to describe the mechanisms of senescence and mitotic catastrophe when present. Results: The primary effect of AXI on LC cell lines is to arrest tumor growth through an indirect DNA damage. Notably, AXI triggers this response in diverse manners among the cell lines, such as inducing senescence or mitotic catastrophe. The drug seems to lose its efficacy when the DNA damage is mitigated, as observed in NCI-H835 cells. Conclusions: The ability of AXI to affect cell viability and proliferation in LC tumor cells highlights its potential as a therapeutic agent. The role of DNA damage and the consequent activation of senescence seem to be a prerequisite for AXI to exert its function.